2011
DOI: 10.5897/ajpp10.243
|View full text |Cite
|
Sign up to set email alerts
|

High phenolics and antioxidants of some tropical vegetables related to antibacterial and anticancer activities

Abstract: Phytochemicals play an important role in the decrease risk of free radicals associated diseases. In the present study, total phenolic contents, antioxidant, antibacterial and anticancer activities of thirty Thai vegetables have been evaluated. The results showed that phenolic contents of Thai vegetables were highly correlated with total antioxidant activities. Four vegetables in strains of Spondias pinnata Kurz., Careya sphaerica Roxb., Caesalpinia mimosoides Lamk. and Cratoxylum Subsp. Pruniflorum (Kurz.) Gog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
5
16
0
2
Order By: Relevance
“…against oral cavity cells but not normal cells is suggestive of preventive roles in cancer (Daduang et al, 2011). This study also demonstrated that the active fractions from C mimosoides Lamk enhanced killing of high-risk HPVpositive and HPV-negative cells.…”
Section: 449 Cytotoxic Effects Of Phytophenolics From Caesalpinia MIsupporting
confidence: 49%
See 2 more Smart Citations
“…against oral cavity cells but not normal cells is suggestive of preventive roles in cancer (Daduang et al, 2011). This study also demonstrated that the active fractions from C mimosoides Lamk enhanced killing of high-risk HPVpositive and HPV-negative cells.…”
Section: 449 Cytotoxic Effects Of Phytophenolics From Caesalpinia MIsupporting
confidence: 49%
“…Several studies revealed that these phenolic compounds have some biological properties, such as anti-oxidant, anti-microbial and anti-cancer activities (Chanwitheesuk et al, 2007;Kim, 2007;Frampton et al, 2010;Lu et al, 2010;Daduang et al, 2011;Hahnvajanawong et al, 2011;Niknafs, 2011;Sakong et al, 2011;Kim and Lee, 2012). Caffeine is thought to increase the anti-tumor effect of cisplatin or DNA-damaging agents because caffeine inhibits DNA repair.…”
Section: 449 Cytotoxic Effects Of Phytophenolics From Caesalpinia MImentioning
confidence: 99%
See 1 more Smart Citation
“…Total phenolic content of crude extracts were determined according to a modified method of Daduang et al (2011). All crude extracts were dissolved in 5%DMSO and final concentration was adjusted to 1 mg/mL.…”
Section: Determination Of Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Some recent studies have assessed the phenolic content of various medicinal and food plants and their related antioxidant properties (e.g., Basar et al 2013;Choudhary and Swarnkar 2011;Daduang et al 2011;Haminiuk et al 2012, Maisuthisakul et al 2007. Though most studies showed a significant relationship between phenolic content and antioxidant properties in vitro, the actual bioavailability of phenolic compounds after digestion is uncertain (Manach et al 2004).…”
Section: Plant Phenolic Compoundsmentioning
confidence: 99%